Extraction, Enrichment, and Quantification of Main Antioxidant Aglycones of Flavonoids and Tannins from Melastoma Dodecandrum Lour.: Guided by UPLC-ESI-MS/MS. (3rd November 2019) - Tong, Yingpeng; Jiang, Yu; Chen, Xubo; Li, Xiaonan; Wang, Ping; Jin, Ye; Cheng, Kejun
Abstract : The objective of this work was to determine the main antioxidant aglycones of flavonoids and tannins in antioxidant extracts from Melastoma dodecandrum Lour. (MD), based on its extraction and purification process optimization and component identification by UPLC-ESI-MS/MS. Firstly, the ultrasound-assisted extraction (UAE) process for antioxidants was established by using single factor tests and response surface optimization. Evaluating by DPPH radical scavenging assay, the antioxidant capacity of MD could reach 2742.27 ± 93.86 ( μ mol Trolox/g) under the optimized conditions including methanol concentration (61%, v/v), extraction time (45 min), liquid-solid ratio (0.46 ml/mg), and extraction temperature (25°C). Then, the antioxidants in the solution were enriched by using macroporous resins. Because of the highest adsorption capacity and desorption ratio, HPD 500 was selected out of 14 macroporous resins for further study based on the static adsorption and desorption tests. The adsorption mechanism of the HPD 500 resin presented that pseudo-first-order kinetics model and Freundlich isotherm model could adequately explain the adsorption process. After the antioxidants were dynamically saturated by HPD 500, the column was eluted with different concentrations of ethanol (0, 25, 50, 75, and 100%, v/v). Among the above five ethanol fractions, 50% ethanol fraction showed the strongest antioxidant activity and more than 95% antioxidants adsorbed in HPD500 could be eluted by 75% ethanol. Guided by analysis results of UPLC-ESI-MS/MS, main antioxidant aglycones of flavonoids and tannins in each ethanol elution fraction were quantitatively detected. Finally, according to the correlation analysis between the antioxidant capacity of each ethanol elution fraction and its content of 10 main flavonoids and phenolic acids, the antioxidant activities of MD could mainly contribute to tannins containing phenolic units such as ellagic acid and/or gallic acid. The results of this work would provide useful information for the production of antioxidants from MD. Thus, the analysis methods could also be a quality control tool for material or products related with MD.